Early embryonic exposure of ionizing radiations disrupts zebrafish pigmentation. Issue 1 (24th August 2018) - Wang, Yupei; Zhou, Xin; Zhao, Baoquan; Ren, Xiaotang; Chen, Yuhong; Si, Jing; Zhou, Rong; Gan, Lu; Zhang, Hong
Abstract : Studies have demonstrated that zebrafish are powerful tools for monitoring environmental toxicity, including radiation hazard. Here we investigated the developmental toxicity of ionizing radiation (IR) in an in vivo embryonic zebrafish model. The effects of heavy ion ( 12 C 6+ ), proton, and X‐ray radiation on early zebrafish embryos were determined. A similar dose‐dependent decrease in the hatch and survival rate of zebrafish embryos was observed after exposure to these irradiations. Exposure of zebrafish embryos to 1–4 Gy IR caused significant loss of pigmentation. Quantitative real‐time reverse transcription polymerase chain reaction, western blot analysis, and in situ hybridization (ISH) experiment revealed that atp5α1 was markedly upregulated in irradiated zebrafish embryos. In addition, IR resulted in a rapid decrease in total adenosine triphosphate (ATP) generation. With dual functions of synthesizing or hydrolyzing ATP, ATP synthase regulated H + transport crossing the mitochondrial inner. Administration of the mitochondrial ATP synthase inhibitor, oligomycin, partially restored pigmentation in irradiated zebrafish embryos, but the ATPase inhibitor, BTB06584, had no effect. Taken together, these results showed that IR exposure downregulated zebrafish pigmentation through regulation of H + ion transport in mitochondria. Abstract : This study provides the first data to indicate that developmental exposure to different types and doses of ionizing radiation (IR) interrupts zebrafish pigmentation and related gene expression. IR exposure downregulated zebrafish pigmentation through regulation of H + ion transport in mitochondria.